An Analysis of Senior High School Students' Listening Factors in Learning Listening - Yasmee, Miranda; Herlina, Rina; Irianti, Leni (Universitas Galuh, 2025)
This study investigates students' behavior in English class when learning to listen. Using qualitative paradigm with the type of case study, this study employed 15 students as participants from the Eleventh Grade of Islamic Senior High School in Ciamis, Indonesia. The instrument of the research involved classroom observations; open-ended and semi-structured interviews administered to teachers to explore students’ behavior in learning to listen in English class. Coding and reducing data entailed selecting and simplifying data, and classifying the remaining data into more specific categories are data analysis of this research. These themes included incorporating listening practice into English learning, providing a comprehensive approach to language acquisition, and helping students build a solid foundation for effective communication and comprehension. The research findings based on the information gathered reveal that students' behavior during listening activities in English learning can vary, but certain patterns and tendencies are commonly observed. Understanding these behaviors can help educators tailor their teaching methods to better support students. The analysis of student listening behavior in learning English includes, among others, active engagement, listening strategies, reaction to difficulty, use of supplementary resources, behavioral adaptations, interaction and feedback, responses, frustration, and satisfaction. By understanding these behaviors, educators can address students' needs more effectively, adapt teaching methods to improve listening skills and overall language proficiency, and offer significant benefits that can greatly enhance a student's language acquisition.